Opportunities and challenges to the sustainable development of cattle raising in Brazil, 1970-2005 - Eustaquio Reis (EconomiA, 2017)
The paper provides historical and analytical perspectives for the assessment of the challenges and opportunities of cattle raising activities in the transition toward a low-carbon agriculture in Brazil. It is organized as follows. The first section poses the problem. The second presents long run historical perspectives on the development of cattle raising in Brazil. The third section analyzes the patterns of growth of cattle raising in Brazil based upon municipal panel data of Agricultural Census from 1975 to 2006. The fourth section uses a framework analogous to Hayami and Ruttan (1985) to estimate growth convergence equations for major aspects of cattle raising activities, namely the stocking ratio, the specialization in cattle and farm expansion. The report concludes with a discussion of policy options for a transition toward sustainable cattle raising in Brazil. – – O trabalho prop\~oe perspectivas histórica e analítica para uma avaliaç\~ao dos desafios e oportunidades da pecuária no processo de transiç\~ao para uma agricultura de baixo carbono no Brasil. Após a introduç\~ao, a segunda seç\~ao apresenta perspectivas históricas sobre o desenvolvimento secular da pecuária brasileira. A terceira seç\~ao analisa os padr\~oes de crescimento da pecuária no Brasil com base em dados municipais dos Censos Agropecuários de 1975 a 1996. A quarta seç\~ao utiliza um esquema analítico análogo ao modelo de Hayami e Ruttan (1985) para estimar equaç\~oes de convegência de crescimento das principais dimens\~oes das atividades pecuárias, quais sejam, a intensificaç\~ao das pastagens, o grau de especializaç\~ao na pecuária e a expans\~ao da atividade agrícola. O trabalho conclui com uma discuss\~ao das opç\~oes políticas na transiç\~ao para pecuária sustentável no Brasil.
Keywords: Q15; Q23; C33; 330; Panel data; Arrellano-Bond; Agricultural economics; Land use; Cattle ranching; Deforestation